Perencanaan Dan Perancangan Day Care Center Di Kota Negara-Jembrana Bali - Annastashya Ramadhani; Gde Bagus Andhika Wicaksana; I Ketut Sugihantara (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Day Care is an institution for child care that can help the role of parents in caring for children at certain times when their parents are busy or don't have much time to care for their children. Generally, Day Care is not only a daycare center but also includes games and lessons that are appropriate for the child's age. Playing and learning activities that are applied to children are the right stimulation for children in stimulating the mind to utilize the social and emotional aspects of children towards the surrounding environment. Some experts also state the importance of educating children from toddlers and the advantages of Day Care lie in cleanliness, facilities, quality and quantity of caregivers and the health of the surrounding environment.